Medicolegal Aspect of Consent - Muhammad Mushtaq, Zoya Imran, Imran Jawaad, Urva Maryum, Humaira Mukhtar, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Consent is a legal requirement for all medical procedures whether surgical or non-surgical. Different types of consents are discussed in books, all fulfill legal requirements which totally depends upon the nature and type of case under process. Objective: Main objective of the study is to determine the awareness of public about consent and its legal value. Material and Method: It is a cross sectional observational study conducted at orthopedic department of Services Hospital Lahore, from 1st January 2019 to 29th December, 2019. A total of 125 patients were selected for this study. Study design: It is a cross sectional observational study. Setting: Study was conducted in the orthopedic department of Services Hospital Lahore. Duration: Study was conducted from 1st January 2019 to 29th December 2019. Data Collection: Data was collected through a questionnaire which was modified after pilot study. Results: Majority 60% of the patients believe that consent is a formality for any medical procedure. 76% of the patients have a feeling that consent is a medical document and has no legal value. 40% of the patients believe that by signing consent they forgive their right for any compensation. 48% of patient’s view consent as protection of their rights whereas 36% of them are unaware about this fact. Conclusion: This study concludes the ignorance of the people about the legal value of consent. A vast gap exists between the informed consent and the knowledge of the people signing this document. In the current situation inform consent need to be modified so that public should be aware about its importance. Keywords: Consent